Pengembangan Buku Digital Tata Bahasa Arab Berbasis Media Digital untuk Jenjang Madrasah Tsanawiyah - Salma, Kunti Nadiyah (Aphorisme: Journal of Arabic Language, Literature, and Education, 2025)
This study aims to develop a digital Arabic grammar book for the Book Creator application, suitable for Arabic language learning at the Madrasah Tsanawiyah level. The background of this study lies in the need for interactive, engaging learning media that align with technological advancements and the characteristics of the digital-native student generation. This research uses the Research and Development (R&D) method with the ADDIE development model. The primary data sources were Arabic language teachers and 10th-grade students at MAN Pacitan. In contrast, the secondary data sources comprised supporting documents such as the 10th-grade Arabic textbooks, student data, and articles related to the research theme. The instruments used in this study included questionnaires, interviews, observations, and tests. The results show that the digital book developed with the Book Creator application is feasible, as evidenced by validation from subject matter experts, media experts, and student trials. This digital book has been shown to increase learning motivation, facilitate the understanding of Arabic grammar concepts, and provide a more interactive and enjoyable learning experience. Thus, developing this digital book can be an innovative solution to improve the quality of Arabic language learning at the Madrasah Aliyah level.